Impression Management Tactics Employed by Primary school Heads to Influence Management and Leadership Decisions in Schools: A Survey of Two Districts in Zimbabwe - Shoko, Shepherd; Dzimiri, Wonderful (Advances in Social Sciences Research Journal, 2018)
Of late, there has been increased research interest in impression management tactics in employment interviews. This study took a detour and investigated impression management tactics used by primary school heads to influence management and leadership decisions in their schools. Underpinned by a mixed methods paradigm, a descriptive survey research design was used wherein fifty selected school heads from two districts in Zimbabwe participated in the study. The school heads responded to a questionnaire and interviews. Data revealed that school heads used self promotion, Association, ingratiation, exemplification, supplication, and intimidation tactics in rank order respectively, to build impressions around their leadership capabilities. A major conclusion was that, these impression management tactics are used differently in different organisation types. It was recommended that the study of impression management in educational leadership and management, which is currently receiving peripheral attention, should be foregrounded to enhance the practice of leadership and management in education.